Installing, Maintaining, and Using a Local Copy of BLAST for Compute Cluster or Workstation Use. Issue 1 (31st August 2018) - Ladunga, Istvan
Abstract: The Basic Local Alignment Search Tool (BLAST) is the first resource to computationally characterize a novel amino acid or nucleic acid sequence. BLAST plays important roles in genomics, transcriptomics, and protein science. For numerous academic and commercial researchers, neither BLAST Web servers nor cloud resources satisfy the requirements of high‐throughput comparative genomic pipelines or company policies. For such users, this unit describes how to install BLAST locally, either on a standalone workstation, or preferably on a compute cluster. We provide practical guidance for the planning and the installation under the LINUX, Windows, and Mac OS X operating systems. We propose strategies for downloading existing and generating new sequence databases in BLAST format. © 2018 by John Wiley & Sons, Inc.